Staroe i novoe Staroye i novoye (Generalnaya liniya ) Staroye i novoye a.k.a. Generalnaya liniya . The General Line - Eisenstein, Sergei; Aleksandrov, Grigori (Amkino ; Sovkino, 1929)
Duration: 02:01:00 The project for this movie was first initiated in 1927, when Sergei Eisenstein created The General Line (Generalnaia linia) to celebrate the campaign for collectivization in the Soviet Union. Hoping to reach a wide audience, the director forsook his usual practice of emphasizing groups by concentrating on a single rural heroine. Eisenstein briefly abandoned this project to film October, in honor of the 10th anniversary of the Revolution. By the time he was able to return to General Line, the Soviet Union was going through the first weaves of Stalinist purges. The intial version of the movie was accussed of having a Trotkist approach. As a result, the film was hastily re-edited and sent out in 1929 under a new title, The Old and the New (Staroe i novoe). In later years, archivists restored The General Line to an approximation of Eisenstein's original concept.